Physicochemical Properties and Yield of Tomato Varieties under Plastic House Condition - Tiwari, Dev N.; Adhikari, Ram C.; Shrestha, Man B. (Nepal Journal of Science and Technology, 2015)
Seven tomato varieties, Ahmita, BL-410, Ceres, Dalila, Makish, Srijana and Winsari were evaluated for physicochemical properties and fruit yield under plastic house condition during rainy seasons of two consecutive years 2012 and 2013 at the Regional Agriculture Research Station, Lumle, Kaski . The experiment was laid out in a complete randomized block design with four replications. The physicochemical analyses revealed that BL-410 had the highest total soluble solid (5.22 oBx) while Srijana had the highest tritrable acidity (0.903%) and vitamic C content (32.32 mg/100 g). It showed that Srijana was the most useful variety from nutritional perspective. BL-410 took least time to flowering (22.00 days), fruiting (28.00 days) and first harvesting (72.00 days) after transplanting. Ahmita produced maximum number of fruits per cluster (8.43). Ceres produced largest size (122.0 g) fruit while Winsari measured the tallest plant (120.5). Winsari produced highest marketable yield (105.8 t ha-1). Thus, it has been recommended for commercial production. Srijana, which has highest nutritional value needs to be promoted with increasing its productivity. DOI: http://dx.doi.org/njst.v15i2.12106 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 17-22